Misogyny Behaviour in Miriam Toews’ Woman Talking - Dahlan,; Mappewali, Nur Ainum (Journal of Islamic Culture and Literature (JICeL), 2024)
The inherent stereotype of society in which women are second-class beings, where women are placed in unimportant positions is one understanding that still triggers the existense of misoginy nowadays. This is in line with the main topic of the novel Woman Talking written by Miriam Toews. Hence, this study discussed the form of Misogyny's Behavior in the Novel "Woman Talking". the purpose of the study is to determine the form of behavior of Misogyny in the novel felt by the women characters. To present accurate data of the phenomenon, the researcher collects all sources related to material objects and formal objects. Researchers used the Misogyny problem as a formal object and used the novel "Woman Talking" by Miriam Toews as a material object. Researchers used Michael Ryan's gender theory to identify problem formulations. By using the Qualitative research method, this research can obtain the result that Behavior of Mysoginy was found through gender injustices experienced by some Molostchna women, they are Subordination, Marginalization, stereotypical, workload and Violence, specifically to the kind of violence, there are 2 types shown which are rape and physical attack.